Toothwear : the ABC of the worn dentition - Khan, Farid; Young, William George, 1939- (Chichester, West Sussex, UK : Wiley-Blackwell Pub., 2011)
This is one of the first books to provide a clinically focussed account of the diagnosis, prevention and treatment of all forms of toothwear. Bringing together the latest research, it is compiled by international leaders in the field to create an essential clinical guide for dental practitioners. The book covers all forms of toothwear and dental erosion, and is presented in a practical format that allows for ease of reference and helps assimilate clinical information quickly. It defines the stages of toothwear, provides schematic approaches to allow better understanding of the key role that sa.
The multifactorial nature of toothwear / F Khan and W Young -- Diagnosis and management of toothwear in children / K Seow and S Taji -- Childhood diet and oral health / L Brearly Messer and W Young -- The oral presentation of toothwear in adults / W Young and F Khan -- Salivary protection against toothwear and dental caries / C Dawes -- The dental medicine of toothwear / W Young and C Dawes -- Preventive and management strategies against toothwear / F Khan and W Young -- Measurement of severity and progression of toothwear / W Douglas and W Young -- Biomaterials and synthetic substitutes / S Bayne -- The role of toothwear in occlusion / A Johansson and G Carlsson -- Restoration of the worn dentition / I Meyers and F Khan -- Rehabilitation of the worn dentition / R Omar and AK Johansson.
Includes bibliographical references and index.
Print version record.
Keywords: Teeth -- Abrasion; Tooth Wear -- diagnosis; Dental Restoration, Permanent -- methods; Tooth Wear -- prevention & control; Tooth Wear -- rehabilitation; Electronic books